2021
DOI: 10.46328/bestdergi.51
|View full text |Cite
|
Sign up to set email alerts
|

Cinsiyetin Öğretmen Motivasyonu Üzerindeki Etkisinin İncelenmesi: Bir Meta-Analiz Çalışması

Abstract: Bu çalışmada cinsiyetin öğretmen motivasyonu üzerindeki rolünü meta-analiz yöntemiyle ile ortaya koymak amaçlanmıştır. Bu doğrultuda öncelikle 2009- 2020 yılları arasında eğitim bilimleri alanında yayınlanmış olan lisansüstü tezlere ilişkin literatür taraması sonucu ulaşılan 27 çalışmadan dâhil etme kriterleriyle çalışmalar ele alınmış ve kriterleri karşılayan 16 bağımsız çalışmayla analizler yapılmıştır. Meta-analiz sonucunda; öğretmen motivasyonunun cinsiyete göre anlamlı farklılaşmadığı tespit edilmiştir (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In their study, where they analyzed 27 studies on the subject, Yarım and Ada (2021) found that male and female teachers had similar qualifications in terms of motivation factors and levels. Similar to the results of the research, there are studies in the literature that teachers experience more work motivation (Koçak, 2002;Polat, 2010) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, where they analyzed 27 studies on the subject, Yarım and Ada (2021) found that male and female teachers had similar qualifications in terms of motivation factors and levels. Similar to the results of the research, there are studies in the literature that teachers experience more work motivation (Koçak, 2002;Polat, 2010) .…”
Section: Discussionmentioning
confidence: 99%
“…One of the areas where individual motivation has been examined in recent years is schools, and researchers have been examining the motivation processes of teachers and educators for many year (Yarım & Ada, 2021). Herzberg (1964) is of the opinion that giving subordinates the opportunity to develop themselves and show their talents and to be given time to achieve success increases the motivation of individuals.…”
Section: Introductionmentioning
confidence: 99%